Effect of Preparation Temperature on the Aging Properties of Waste Polyethylene Modified Asphalt. Issue 3 (March 2015) - Fang, Changqing; Zhang, Mengya; Yu, Ruien; Liu, Xiaolong
Abstract : In this study, waste polyethylene (WPE) was used as a modifier for base asphalt. In our previous studies, we have examined a variety of polymer modifiers for asphalt. By contrast, little research has focused on the preparation process, such as preparation time, preparation temperature and shear rate. The effect of preparation temperature on aging properties of WPE-modified asphalt was investigated in this work. The experimental materials were characterized by infrared spectroscopy (IR), thermo-gravimetric analysis (TG), and differential scanning calorimetry (DSC). The physical properties were determined by conducting asphalt penetration, softening point and ductility tests. The results show that increasing the preparation temperature results in an increased softening point of WPE-modified asphalt while decreased penetration and ductility. In addition, this variation was accentuated by aging the experimental materials. The modification process of WPE is a physical process. During the asphalt modification process, the WPE aged as the preparation temperature increased. The results revealed that 190 °C is the most suitable preparation temperature, and the post aged asphalt demonstrated improved high temperature stability.